Medallion „Librarians in time and space”. The Green Palace Library: About J. W. Goethe (1749-1832) (Confluenţe Bibliologice, 2025)
The article is devoted to the history of the Anna Amalia Library, located in the Green Palace in Weimar, and the role of J. W. Goethe in its development. The library, recognized by UNESCO as a cultural heritage, was founded in 1691. In 1797, Goethe was appointed commissioner of the library and theater, where he implemented many reforms. He increased the book collection to 122 thousand volumes, introduced a system of recording new acquisitions, created catalogs and held book exhibitions, which significantly improved readers' access to information. The article emphasizes that Goethe was not only an outstanding writer, but also a talented librarian who truly loved books and sought to make the library more accessible and structured for readers.
Keywords: Goethe Johann Wolfgang von (1749 – 1832)